"Decolonizing" Curriculum and Pedagogy: A Comparative Review Across Disciplines and Global Higher Education Contexts. (February 2022) - Shahjahan, Riyad A.; Estera, Annabelle L.; Surla, Kristen L.; Edwards, Kirsten T.
Drawing on the global interdisciplinary literature on decolonizing curriculum and pedagogy (DCP) in higher education, we critically examined the idea of decolonizing in the context of disciplines and universities around the world. Based on a critical analysis of 207 articles and book chapters published in English and centering a geopolitics of knowledge frame, we present three themes: (a) decolonizing meaning(s), (b) actualizing decolonization, and (c) challenges to actualizing, all related to DCP. We observed three major meanings of decolonization and four ways to actualize DCP that were associated with geographical, disciplinary, institutional, and/or stakeholder contexts. We argue that while there are similarities within the literature, ultimately the meanings, actualizations, and challenges of DCP are contextual, which has political and epistemological consequences. We end by offering directions for education research on DCP, revealing the possibility for a field or discipline of decolonial studies.